2020
DOI: 10.1002/ece3.6865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of scavenger receptors and thrombospondin‐type‐1 repeat proteins potentially relevant for plastid recognition in Sacoglossa

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 99 publications
(202 reference statements)
1
21
0
Order By: Relevance
“…In mice macrophages, semaphorin positively regulated phagocytosis and the inflammatory response after LPS treatment ( 72 ). In invertebrates, semaphorins are likely involved in detection and phagocytosis of photosymbionts [in cnidarians ( 73 ), in sea slugs ( 74 )]. Sponges rely on phagocytosis for food uptake while depending on differential recognition of their symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…In mice macrophages, semaphorin positively regulated phagocytosis and the inflammatory response after LPS treatment ( 72 ). In invertebrates, semaphorins are likely involved in detection and phagocytosis of photosymbionts [in cnidarians ( 73 ), in sea slugs ( 74 )]. Sponges rely on phagocytosis for food uptake while depending on differential recognition of their symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms utilized by the slugs to selectively sequester plastids from the algae they consume remain uncertain, although recent studies have shown that in E. chlorotica it is an active process reminiscent of that observed for symbiotic algae and corals ( Chan et al , 2018 ). The slugs possibly rely on scavenger receptors and thrombospondin type 1 repeat proteins for plastid recognition ( Melo Clavijo et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms utilized by the slugs to selectively sequester plastids from their prey algae remain uncertain, although recent studies have shown that in E. chlorotica it is an active process reminiscent of that observed for symbiotic algae and corals (Chan et al, 2018). The slugs possibly rely on scavenger receptors and thrombospondintype-1 repeat proteins for plastid recognition (Clavijo et al, 2020). The sacoglossan's ability to sequester plastids tends to distract attention from the unique features of the sequestered organelle, forming the second component of a photosynthetic slug system.…”
Section: Introductionmentioning
confidence: 99%